Sustainability of Energy Conservation in HVAC System Using Fuzzy Logic - Azmi M.H.; Othman M.M.; Rodzi M.S.; Musirin I.; Ahmadipour M. (Penerbit UTHM, 2025)
Nowadays, air-conditioning systems are installed in buildings to provide a healthy and comfortable environment for the occupants. However, it will consume a large amount of energy resulting in an expensive cooling cost in the building. This paper presents an approach to minimize the energy consumption of the heating, ventilation and air conditioning (HVAC) system. The main objective is to provide a solution to reduce the energy consumption of a house air system using fuzzy logic by controlling the expansion valve of the air conditioner. The membership functions of fuzzy logic consisting of two inputs and one output were used as a method to control the output temperature of the system. The output shows a reduction in the cooling cost of the HVAC system in a building. ? (2024), (Penerbit UTHM). All rights reserved.